2000
DOI: 10.1016/s0092-8674(00)00029-5
|View full text |Cite
|
Sign up to set email alerts
|

Zip3 Provides a Link between Recombination Enzymes and Synaptonemal Complex Proteins

Abstract: In budding yeast, absence of the meiosis-specific Zip3 protein (also known as Cst9) causes synaptonemal complex formation to be delayed and incomplete. The Zip3 protein colocalizes with Zip2 at discrete foci on meiotic chromosomes, corresponding to the sites where synapsis initiates. Observations suggest that Zip3 promotes synapsis by recruiting the Zip2 protein to chromosomes and/or stabilizing the association of Zip2 with chromosomes. Zip3 interacts with a number of gene products involved in meiotic recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
446
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(475 citation statements)
references
References 39 publications
26
446
3
Order By: Relevance
“…Notably, the relative number of RAD51 foci associated with ZYP1 decreased over time from 65.4% in leptotene to 36.5% in pachytene (P = 5.6 3 10 210 ) ( Figure 2B). This suggests that RAD51 foci represent nucleoprotein filaments that stay predominantly axis-associated and furthermore that ZYP1 is loaded next to RAD51 at DSB sites, as suggested previously (Agarwal and Roeder, 2000). Decreasing total and ZYP1-associated RAD51 foci numbers during meiotic progression could be explained by depletion of RAD51 at sites of successful meiotic DNA repair (Franklin et al, 1999;Allers and Lichten, 2001;Bugreev et al, 2010).…”
Section: Rad51 and Dmc1 Do Not Colocalize And Form Homotypic Foci Dursupporting
confidence: 68%
“…Notably, the relative number of RAD51 foci associated with ZYP1 decreased over time from 65.4% in leptotene to 36.5% in pachytene (P = 5.6 3 10 210 ) ( Figure 2B). This suggests that RAD51 foci represent nucleoprotein filaments that stay predominantly axis-associated and furthermore that ZYP1 is loaded next to RAD51 at DSB sites, as suggested previously (Agarwal and Roeder, 2000). Decreasing total and ZYP1-associated RAD51 foci numbers during meiotic progression could be explained by depletion of RAD51 at sites of successful meiotic DNA repair (Franklin et al, 1999;Allers and Lichten, 2001;Bugreev et al, 2010).…”
Section: Rad51 and Dmc1 Do Not Colocalize And Form Homotypic Foci Dursupporting
confidence: 68%
“…2A; Peoples et al 2002). Msh4 has been reported to colocalize with Msh5 (Agarwal and Roeder 2000). Accordingly, we found that an msh4⌬ single mutant also exhibited the same level of allelic interactions as msh5⌬ and wild type ( Fig.…”
Section: Cre/loxp Recombination Indicates Allelic Interactionssupporting
confidence: 62%
“…PCR was used to introduce a NotI site $290 bp upstream of the OSW1 ORF and an NheI site just before the stop codon. The NotI-NheI fragment ($1.1 kbp) containing OSW1 was subcloned into the NotI-NheI sites of pSA111 (Agarwal and Roeder 2000) to create pJ83, which contains GFP fused to the 39 end of OSW1.…”
Section: Methodsmentioning
confidence: 99%